Borrelia burgdorferi genospecies detection by RLB hybridization in Ixodes cinus ticks from different sites of North-Eastern Poland - Justyna Dunaj; Joanna Maria Zajkowska; Maciej Kondrusik; Lise Gern; Oliver Rais; Anna Moniuszko; Sławomir Pancewicz; Renata Świerzbińska (Annals of Agricultural and Environmental Medicine, 2014)
Introduction. RLB (Reverse Line Blot Hybridization) is a molecular biology technique that might be used for [i]Borrelia burgdorferi [/i]sensu lato (sl) DNA detection with genospecies specification. Among[i] B. burgdorferi[/i] sl genospecies at least 7 are regarded as pathogenic in Europe. objective. The aim of the study was to evaluate the frequency of different [i]Borrelia[/i] genospecies DNA detection in Ixodes ricinus ticks in the endemic area of North-Eastern Poland by using RLB. materials and method. Ixodes ricinus ticks were collected in May – June, from 6 different sites in North-Eastern Poland (Jakubin, Kolno, Grajewo, Suwałki, Siemiatycze, Białowieża) by flagging. Extracted DNA was amplified by polymerase chain reaction (PCR) targeting the intergenic spacer 5S 23S of [i]B. burgdorferi sl.[/i] PCR products were hybridised to 15 different oligonucleotide probes for 9 different [i]Borrelia [/i]genospecies ([i]B. burgdorferi sl, B. burgdorferi ss, B. garinii, B. afzelii, B. valaisiana, B. lusitaniae, B. spielmanii, B. bissettii and B. relapsing[/i] fever-like spirochetes (B. myamotoi)) by RLB. results. [i]Borrelia [/i]genospecies DNA was detected in 205 Ixodes ricinus ticks. Among 14 infected with [i]Borrelia[/i] ticks, 4 were identified as B. garinii and 10 as B. afzelii. Higher numbers of infected ticks were noticed in the eastern part of the research area, where large forest complexes dominate. Nymphs appeared to be the most frequently infected tick stage, which has an epidemiological meaning in the incidence of Lyme borreliosis. conclusions. The study demonstrated that RLB might be easily used in [i]Borrelia[/i] DNA detection with genospecies-identification, and indicated the domination of [i]B. afzelii and B. garinii [/i]in ticks from North-Eastern Poland.